The effect of stirring on the heterogeneous nucleation of water and of clathrates of tetrahydrofuran/water mixtures - Wilson, P.W.; Haymet, A.D.J. (Condensed Matter Physics, 2016)
The statistics of liquid-to-crystal nucleation are measured for both water and for clathrate-forming mixtures of tetrahydrofuran (THF) and water using an automatic lag time apparatus (ALTA). We measure the nucleation temperature using this apparatus in which a single sample is repeatedly cooled, nucleated and thawed. The effect of stirring on nucleation has been evaluated numerically and is discussed. We find that stirring of the solution makes no difference to the nucleation temperature of a given solution in a given tube. Вимiрюється статистика нуклеацiї рiдина-до-кристалу для води i для граткоформуючих сумiшей тетрагiдрофурану та води, використовуючи апарат автоматичної часової затримки (ALTA). Ми вимiрюємо температуру нуклеацiї, використовуючи цей апарат, в якому той самий зразок повторювально охолоджується,
проходить нуклеацiю i розплавлюється. Ефект перемiшування на нуклеацiю був оцiнений чисельно i дискутується. Ми отримали, що перемiшування не дає ефекту для температури нуклеацiї даного розчину в
данiй комiрцi.